Comparison of gemcitabine and carboplatin versus cisplatin and etoposide for patients with poor-prognosis small cell lung cancer. Issue 1 (11th September 2008) - Lee, S M; James, L E; Qian, W; Spiro, S; Eisen, T; Gower, N H; Ferry, D R; Gilligan, D; Harper, P G; Prendiville, J; Hocking, M; Rudd, R M
Abstract : Background: The combination of cisplatin and etoposide (PE) has been a standard treatment for patients with poor-prognosis small cell lung cancer (SCLC). This non-inferiority design trial aimed to determine whether the combination of gemcitabine and carboplatin (GC) results in similar survival but is less toxic with better quality of life. Methods: Previously untreated patients with SCLC with extensive disease or limited stage with poor prognostic factors were randomly assigned to six 3-weekly cycles of GC or PE. Results: 241 patients (121 GC, 120 PE) were recruited, of which 216 (90%) had died. There was no difference in overall survival (HR 1.01, 95% CI 0.77 to 1.32). Median survival with GC and PE was 8.0 and 8.1 months, respectively. Median progression-free survival was 5.9 months with GC and 6.3 months with PE. Grade 3 or 4 myelosuppressions were more frequent with GC (anaemia: 14% GC vs 2% PE; leucopenia: 32% GC vs 13% PE; thrombocytopenia: 22% GC vs 4% PE), but these were not associated with increased hospital admissions, infections or fatalities. Grade 2–3 alopecia (68% PE vs 17% GC) and nausea (43% PE vs 26% GC) were more frequent with PE. Patients given GC received more chemotherapy as outpatients (89% GC vs 66% PE of treatment cycles). In QoL questionnaires, more patients receiving PE reported being upset by hair loss (p = 0.004) and impaired cognitive functioning (p = 0.04). Conclusions: GC is as effective as PE in terms of overall survival and progression-free survival and has a toxicity profile more acceptable to patients. Trial registration number: ISRCTN 39679215